Vertical Infections and Prevalence of Viral Nervous Necrosis (VNN) in Milkfish (Chanos chanos) - Sang Ayu Made Putri Suryani; Ni Made Darmadi; Made Goura Premananda; Gusti Ngurah Permana (Journal of Aquaculture and Fish Health, 2022)
Milkfish juvenile is the leading fishery species in Bali with an export value in 2019. The increase in demand is related to the intensification of aquaculture which causes various diseases, especially Viral Nervous Necrosis (VNN). VNN infection in juveniles has been through water media. The VNN infection in milkfish may occur vertically. This study aims to determine the vertical infection and prevalence of VNN in milkfish. The VNN examination was carried out using the reverse transcription real-time Polymerase Chain Reaction (rRT-PCR) method. This research was conducted at BKIPM Denpasar. Samples were milkfish eggs taken from 15 spawning ponds in Gerogak District, Buleleng Regency. The results showed 3 positive samples from the 15 samples tested. A4 VNN positive sample with Ct 39.29 showed a virus concentration of 146 copies, Sample F positive for VNN with Ct 38.79 showing the 1978 copies of virus concentration, Sample G was positive for VNN with Ct 39.16 showing a virus concentration of 1588. Positive results of VNN examination on milkfish eggs with real time PCR indicates the presence of vertical transmission of VNN. It is also supported by measurement of water quality in milkfish spawning ponds shows the parameters of temperature, DO and pH in optimal and appropriate conditions standard. The results of the observation of clinical symptoms also show the condition of milkfish in a healthy state seen from swimming behavior that does not show symptoms of VNN infection. there are 3 positive samples in sample A4 with a virus concentration of 1,466 copies, sample F with a virus concentration of 1,978 copies and sample G with a virus concentration of 1,588. Detected VNN in eggs milkfish showed vertical VNN infection. Prevalence of infection. Milkfish egg against VNN shows a value of 20% which is included in the frequent infection category.